Korelasi Antara Indeks Prestasi Kumulatif dan Nilai Praktek Pengalaman Lapangan Mahasiswa - Tomi, Zebbil Billian; Nuryanuwar, Nuryanuwar (Lattice Journal : Journal of Mathematics Education and Applied, 2022)
This study aims to determine the correlation of the Cumulative Grade Point Average (GPA) with the value of Student Field Experience Practice (PPL) of FTIK UIN Sjech M. Djamil Djambek Bukittinggi students. This research includes ex post facto correlational research. The population in this study were all participants in the Field Experience Practice (PPL) of the Faculty of Tarbiyah and Teacher Training at UIN Sjech M. Djamil Djambek Bukittinggi in 2021, a total of 538 people. The sample size of the study was 54 people determined by simple random sampling technique. The data in this study are in the form of a Cumulative Grade Point Average (GPA) with the value of Student Field Experience Practice (PPL) for FTIK UIN Sjech M. Djamil Djambek Bukittinggi students in 2021. Using correlation analysis of the Spearmans Rho test a significant value was obtained between the Cumulative Grade Point Average (GPA) and the value of Student Field Experience Practice (PPL) is 0.978. The results of the study showed that there was no significant correlation between the Cumulative Grade Point Average (GPA) and Field Experience Practice Scores (PPL) of FTIK UIN Sjech M. Djamil Djambek Bukittinggi students in 2021.Penelitian ini bertujuan untuk mengetahui korelasi Indeks Prestasi Komulatif  (IPK) dengan nilai Praktek Pengalaman Lapangan Mahasiswa (PPL) mahasiswa FTIK UIN Sjech M. Djamil Djambek Bukittinggi. Penelitian ini termasuk penelitian korelasional expost facto. Populasi dalam penelitian ini adalah seluruh peserta Praktek Pengalaman Lapangan (PPL) Fakultas Tarbiyah dan Ilmu Keguruan UIN Sjech M. Djamil Djambek Bukittinggi tahun 2021 yang berjumlah 538 orang. Ukuran sampel penelitian sebanyak 54 orang ditentukan dengan teknik simple random sampling. Data pada penelitian ini berupa Indeks Prestasi Komulatif  (IPK) dengan nilai Praktek Pengalaman Lapangan Mahasiswa (PPL) mahasiswa FTIK UIN Sjech M. Djamil Djambek Bukittinggi tahun 2021. Dengan menggunakan analisis korelasi Uji Spearmans Rho diperoleh nilai signifikan antara Indeks Prestasi Komulatif  (IPK) dengan nilai Praktek Pengalaman Lapangan Mahasiswa (PPL) yaitu 0.978. Hasil penelitian menunjukkan bahwa tidak ada korelasi yang signifikan  antara Indeks Prestasi Kumulatif (IPK) dan Nilai Praktek Pengalaman Lapangan (PPL) mahasiswa FTIK UIN Sjech M. Djamil Djambek Bukittinggi tahun 2021.